Electronic document management at the Federal University of Uberlândia (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
The modernization of administrative processes in Brazil, with the transition from analogue to digital, has brought significant advances, but still reveals gaps in the management of electronic documents. This study investigated the management of these documents in the Electronic Information System of the Federal University of Uberlândia, using document analysis. The research found that the processes in the system only cover the production and classification phases, without document evaluation. The study highlights the urgent need to develop criteria to evaluate and subsequently eliminate or permanently preserve documents produced within the system.
Keywords: administrative modernization; document management; Electronic Information System